Restoring crown fractures by direct composite layering using transparent strip crowns. Issue 2 (8th October 2015) - Eden, Ece; Taviloğlu, Engin
Abstract: Traumatic dental injuries are mostly seen at childhood and adolescence. The most common fracture in permanent anterior teeth is crown fracture. Esthetic and easy rehabilitation of these anterior teeth is possible using layering techniques and direct composite resin restorations. Shape, color and surface texture are the most important factors in restoring crown fractures esthetically. This article illustrates how to perform an esthetic composite resin restoration of crown fractures using strip crowns. The technique suggests using a strip crown as a mold for direct resin composite restoration. This provides a cost‐effective treatment with operator friendly approach where most outstanding advantage is the minimum chair‐side time with a single visit that is very important for young trauma patients.